2022
DOI: 10.3389/fmolb.2022.914506
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA NBAT1, TUG1, miRNA-335, and miRNA-21 as potential biomarkers for acute ischemic stroke and their possible correlation to thyroid hormones

Abstract: Objective: RNA-based mechanisms of epigenetic modification related to acute ischemic stroke (AIS) have been widely studied recently. The current work aimed to determine the potential roles of four ncRNAs (TUG1 and its target miR-21, NBAT1, and miR-335) as promising diagnostic biomarkers in AIS as well as their involvement in the disease pathogenesis.Methods: The levels of the studied lncRNAs and miRNAs were measured in the serum for two different groups, including patients with AIS (60) and healthy controls (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The transcriptomics of PSCI has also highlighted the effectiveness of certain miRNAs in terms of diagnosis, including miR-21, miR-132, miR-195, miR-200b, miR-497, and miR-let-7i. Thus far, research has validated the molecular diagnostic capability of miR-21 in several diseases such as acute cerebral infarction ( Mohammed et al, 2022 ), atherosclerosis ( Fontanella et al, 2021 ), and glioma ( Zhou et al, 2018 ). Other studies have identified the diagnostic properties of miR-132 in mild cognitive impairment ( Sheinerman et al, 2012 ; Xie et al, 2015 ) due to its modulation of glutamate receptor levels.…”
Section: The Clinical Application Prospect Of Multi-omics In Pscimentioning
confidence: 99%
“…The transcriptomics of PSCI has also highlighted the effectiveness of certain miRNAs in terms of diagnosis, including miR-21, miR-132, miR-195, miR-200b, miR-497, and miR-let-7i. Thus far, research has validated the molecular diagnostic capability of miR-21 in several diseases such as acute cerebral infarction ( Mohammed et al, 2022 ), atherosclerosis ( Fontanella et al, 2021 ), and glioma ( Zhou et al, 2018 ). Other studies have identified the diagnostic properties of miR-132 in mild cognitive impairment ( Sheinerman et al, 2012 ; Xie et al, 2015 ) due to its modulation of glutamate receptor levels.…”
Section: The Clinical Application Prospect Of Multi-omics In Pscimentioning
confidence: 99%